A formação dos estudantes em discussões sobre tecnologias: uma questão sociocientífica para o ensino de ciências - Coelho Júnior, João Pedro Martins (2022)
Techniques and technologies have helped man to understand and dominate the world around him. The need to facilitate daily life as issues involving work, and later the search for new territories, which contributed to the creation of wars and domination of peoples, helped in the unbridled development of techniques and technologies. However, it is questioned what interests are related to their development, since such interests have several aspects, such as serving to guarantee the progress of humanity, or to destroy and decimate regions and peoples, a fact that puts the ethical and moral issues. Therefore, we believe that scientific and technological training through Education in Science, Technology and Society (STS) is important as a promising factor to assist in the construction of critical thinking and decision-making in relation to the impositions of techniques and technologies. In this way, we developed a didactic sequence for students of the seventh year of elementary school at a state public school in the city of Leme-SP, with the aim of discussing the following research questions: How can we promote education for and with technologies so that it contributes to the scientific and technological training of citizens and what elements can express the training processes of students from STS education? And what are the contributions and limits of a proposal for a didactic sequence, elaborated through STS education and socio-scientific issues, for the teaching of technologies and for the understanding and participation of subjects in science and technology topics? After carrying out the didactic sequence, we used Content Analysis as an analysis tool, proposed by Bardin, to interpret the students' statements throughout the didactic sequence. At the end of the didactic sequence and analyzing the results, we concluded that by encompassing the theme with STS education, students were able to establish relationships of the impacts that technologies have on science and society. By proposing activities on the subject for students to argue and discuss during classes, we were able to observe attitudes and elements that express the formative processes through STS education, such as positioning their decisions regarding techniques and technologies, investigative, questioning spirit and transforming reality, providing the search for solutions to problem-situations that involve them and using them to solve collective problems of their community.